The Effect of Internet Use on the Academic Achievement of Students at SMPN 37 Satap Bentenge in the Remote Village of Benteng - Annisa Amaliah Mulia; Iwan Suhardi; Dwi Rezky Anandari Sulaiman (Journal of Educational Studies in Science, Technology, Engineering, Arts and Humanities, 2026)
This study aimed to determine the effect of internet use on the academic achievement of students at SMPN 37 Satap Bentenge. This study use a quantitative descriptive research design. The data collection techniques used were are interviews, questionnaires, and documentation. The independent variable in this study is internet use, and the dependent variable is academic achievement. This study was conducted in Benteng Village, Camba Subdistrict, Maros Regency, South Sulawesi Province, Indonesia, from August to September 2023. The sample consisted of 30 students from grades VIII and IX of SMPN 37 Satap Bentenge, selected using purposive sampling method. Data analysis was performed using descriptive analysis and the T-test . The results of the study show that based on all of these results, it can be concluded that the use of the internet among students at SMPN 37 Satap Bentenge is in the high category with a percentage value of 36.7% and there is an increase in the average score of students before and after the internet was available, from 79.54 before the internet was available to 80.310 after the internet was available. Based on the results of the Paired Sample T Test, there is a difference in the average scores before and after the introduction of the internet, with a significance value of 0.000. This significance value is <0.05, which means that there is a significant difference between the average scores of students before and after the introduction of the internet. This difference means that internet usage has an effect on learning achievement because the students' scores are significantly different before and after the introduction of the internet.